Early Marriage Based on Transcultural Nursing Theory in Kara Village Sampang - Esti Yunitasari; Retnayu Pradanie; Ayu Susilawati (Jurnal Ners, 2016)
Introduction: The early-age marriage is still happened in the world with many reasons. Early marriage has many negative impacts on education, social, economic, psychological, and reproductive health. The purpose of this study is to analyze the factors of early marriage based on Transcultural Nursing theory. Methods: Design used in this research was cross-sectional approach. The sampel was women who got married between January 2015 and February 2016. The 39 sample respondents were chosen by purposive sampling technique. The independent variables in this study were knowledge, culture, family suport, economic, technology and the dependent variable was early marriage. The data were collected by using questionnaire and analyzed by using chi square test. Results: The results showed significant correlation between cultural factor (p=0.013), family support factor (=0,001), economic factor (p=0,040), and technology factor (p=0,002) with early marriage, while knowledge factor have not significant correlation with early marriage. Discussion: By the result of this study, it was expected there will be some actions together with relevant parties to give health education for adolescent who has married yet to prevent early marriage.